2008
DOI: 10.1152/ajplung.00404.2007
|View full text |Cite
|
Sign up to set email alerts
|

Compromised E-cadherin adhesion and epithelial barrier function with activation of G protein-coupled receptors is rescued by Y-to-F mutations in β-catenin

Abstract: vation of the type 1 histamine (H1) or the type 2 protease-activated (PAR-2) G protein-coupled receptors interrupts E-cadherin adhesion and decreases the transepithelial resistance (TER) of epithelium. Several reports suggest that cadherin adhesive function depends on the association of cadherin with ␤-catenin and that this association is regulated by phosphorylation of tyrosines in ␤-catenin. We tested the hypothesis that loss of cadherin adhesion and compromise of TER on activation of the H1 or PAR-2 recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
(52 reference statements)
2
10
0
Order By: Relevance
“…Consistent with our data, overexpression of claudin-7 in porcine PTCs markedly increases TER, decreases paracellular chloride conductance and increases paracellular sodium conductance (26). E-cadherin expression has also been shown to regulate TER in MDCK cells (27,28). These previous studies support our hypothesis that the increase in TER in the ␤1…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with our data, overexpression of claudin-7 in porcine PTCs markedly increases TER, decreases paracellular chloride conductance and increases paracellular sodium conductance (26). E-cadherin expression has also been shown to regulate TER in MDCK cells (27,28). These previous studies support our hypothesis that the increase in TER in the ␤1…”
Section: Discussionsupporting
confidence: 88%
“…Although it is very possible that these two events are independent of each other and that HER2 impacts cell adhesion through a process independent of Ecadherin, a role for ␤-catenin in regulating E-cadherin cell-cell adhesion is supported by existing literature. ␤-Catenin phosphorylation can be associated with a decrease in ␤-catenin-Ecadherin interaction and E-cadherin-mediated cell-cell adhesion (36,47). Indeed Winter et al (47) demonstrated that G protein receptors influence E-cadherin-mediated adhesion though a process dependent on ␤-catenin tyrosine phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…␤-Catenin phosphorylation can be associated with a decrease in ␤-catenin-Ecadherin interaction and E-cadherin-mediated cell-cell adhesion (36,47). Indeed Winter et al (47) demonstrated that G protein receptors influence E-cadherin-mediated adhesion though a process dependent on ␤-catenin tyrosine phosphorylation. Although the exact mechanisms of how loss of ␤-catenin interaction with E-cadherin regulates its adhesive properties is unknown and not a focus of our study, it has been postulated that loss of catenin-cadherin binding leads to a conformational change in E-cadherin that alters the extracellular E-cadherin-E-cadherin bond (19).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent work by Miyahara et al (6) suggest Src kinase inhibition prevents the ventilatorinduced increase in lung vascular permeability. Overall, the insights provided by Winter et al (10) are significant and can help to guide our forthcoming studies to provide ever more direct insight into the functional control of cell communities, as in the case of adhesion strength among lung epithelial cells.…”
mentioning
confidence: 86%
“…L cells endogenously express PAR-2, and so this receptor was not transfected. Using this model system, Winter et al (10) demonstrated that H1 receptor ligation and PAR-2 activation (e.g., G protein-coupled receptor activation) decreased E-cadherin-dependent adhesion. In both cases, the response required the phosphorylation of ␤-catenin Y489 and Y654 but not Y142.…”
mentioning
confidence: 99%